Testing the Efficacy of Extractives from Chir Pine Needles through Petri Plate Bioassay against Bamboo Decaying Fungi - Sumi, A.; Tripathi, S.; Harsh, N. S. K. (Indian Forester, 2017)
Chir (Pinus roxburghii) pine needles extractives are rich in resin and essential oil. The present study was carried out to evaluate the efficacy of chir pine needles extractives at different concentrations (0.5, 1, 1.5, 2 and 2.5%) against bamboo decaying fungi viz., Hypoxylon fragiforme and Hypoxylon rubiginosum through Petri plate bioassay. The results, revealed an efficacy of chir pine needles extractives in inhibiting the growth of both fungi completely at 2.5% concentration.